2011
DOI: 10.1038/nbt.1846
|View full text |Cite|
|
Sign up to set email alerts
|

Amelioration of sepsis by inhibiting sialidase-mediated disruption of the CD24-SiglecG interaction

Abstract: Control of inflammation is critical for therapy of infectious diseases. Pathogen-associated and/or danger-associated molecular patterns (PAMPs and DAMPs, respectively) are the two major inducers of inflammation. Because the CD24-Siglec G/10 interactions selectively repress inflammatory response to DAMPs, microbial disruption of the negative regulation would provide a general mechanism to exacerbate inflammation. Here we show that the sialic acid-based pattern recognitions of CD24 by Siglec G/10 are targeted by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
186
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(202 citation statements)
references
References 50 publications
7
186
0
3
Order By: Relevance
“…However, Siglec-G is expressed both on conventional DCs and on plasmacytoid DCs, as well as on eosinophils. This finding is of importance, as functions for Siglec-G on these DCs were indicated as important for preventing inflammatory responses in a liver damage model as well as for antibacterial responses (9,10). A recent study also showed that Siglec-G was induced in macrophages by RNA viruses and that this Siglec-G upregulation was important for innate immune responses against RNA viruses (19).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, Siglec-G is expressed both on conventional DCs and on plasmacytoid DCs, as well as on eosinophils. This finding is of importance, as functions for Siglec-G on these DCs were indicated as important for preventing inflammatory responses in a liver damage model as well as for antibacterial responses (9,10). A recent study also showed that Siglec-G was induced in macrophages by RNA viruses and that this Siglec-G upregulation was important for innate immune responses against RNA viruses (19).…”
Section: Discussionmentioning
confidence: 88%
“…A Siglec-G-GFP knockin mouse suggested a broader Siglec-G expression pattern in B cells and several myeloid cell types (8). A functional role of Siglec-G expression on DCs was postulated to be responsible for a Siglec-Gdependent protective effect in a liver injury model and in antibacterial defense (9,10). However, in all of these studies only intracellular expression of Siglec-G was examined because a mAb for determining cell surface expression was not available.…”
Section: The Journal Of Immunologymentioning
confidence: 99%
“…5 By interacting with Siglec-G/10, an immunoreceptor tyrosine-based inhibition motif (ITIM)-containing negative regulator of inflammation, CD24 has been shown to serve as an essential brake for inflammation induced by damageassociated molecular patterns (DAMPs). 6,7 Bacterial and viral-derived sialidases, which were previously considered virulence factors only in the context of pathogen growth, can disrupt the CD24-Siglec-G/10-mediated negative regulation mechanism by de-sialylation, thereby exacerbating bacteriainduced sepsis. 6 CD24 plays important roles in immune regulation by providing co-stimulatory signals to T cells and B cells.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Bacterial and viral-derived sialidases, which were previously considered virulence factors only in the context of pathogen growth, can disrupt the CD24-Siglec-G/10-mediated negative regulation mechanism by de-sialylation, thereby exacerbating bacteriainduced sepsis. 6 CD24 plays important roles in immune regulation by providing co-stimulatory signals to T cells and B cells. 5,8 For example, CD24 is critical for T cell homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that Siglecs play an important role in the internalization of sialic acid-expressing pathogens (17-19), in controlling allergic asthma (20, 21), and in self-tolerance (22). Previously, we found that Siglec G/10-CD24 interaction selectively represses the NF-B-driven inflammatory response to danger-associated molecular patterns (DAMPs), 2 but not pathogen-associated molecular patterns (PAMPs) (23,24 …”
mentioning
confidence: 99%